(untitled) (Gestão & Regionalidade, 2023)
This article analyzes the factors that influence the implementation of the policy of the Attention to the Health and Safety of the Federal Public Server - PASS, in the Federal Institute of Education of Bahia - IFBA, between the years 2011 and 2018. The concepts of public policy and its implementation phase were used. It is a work with quantitative approach, using multiple regression to a sample of 346 answered questionnaires, obtained between August and September 2018. The results show that the PASS is not effectively implemented, evidenced by the lack of knowledge of the servers about its existence and low participation in the developed actions. They also indicate that the contextual variable factors, organizational culture, organization of the administrative apparatus and available resources are those related to the effectiveness in the process of implementation of the policy studied.